2013
DOI: 10.1186/1479-5876-11-118
|View full text |Cite
|
Sign up to set email alerts
|

The role of globular heads of the C1q receptor in HPV 16 E2-induced human cervical squamous carcinoma cell apoptosis is associated with p38 MAPK/JNK activation

Abstract: BackgroundHuman papillomavirus type 16 (HPV 16) E2 protein is a multifunctional DNA-binding protein. HPV 16 E2 regulates many biological responses, including DNA replication, gene expression, and apoptosis. The purpose of this study was to investigate the relationship among the receptor for globular heads of the human C1q (gC1qR) gene expression, HPV 16 E2 transfection and apoptosis regulation in human cervical squamous carcinoma cells (C33a and SiHa).MethodsgC1qR expression was examined in C33a and SiHa cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Early in 2006, Engelbrecht et al indicated the involvement of MAPK in cervical cancer and demonstrated the correlation between the activity of MAPK and apoptosis in the disease process (49). The HPV 16 E2 protein may induce apoptosis by inhibiting MAPK signaling in CSCC (50). However, playing a role in cervical cancer carcinogenesis, the expression level of MAPK may serve as a marker for cervical cancer progression (51,52) and its inhibitors have shown the potential to be useful for cervical cancer therapy (53).…”
Section: Discussionmentioning
confidence: 99%
“…Early in 2006, Engelbrecht et al indicated the involvement of MAPK in cervical cancer and demonstrated the correlation between the activity of MAPK and apoptosis in the disease process (49). The HPV 16 E2 protein may induce apoptosis by inhibiting MAPK signaling in CSCC (50). However, playing a role in cervical cancer carcinogenesis, the expression level of MAPK may serve as a marker for cervical cancer progression (51,52) and its inhibitors have shown the potential to be useful for cervical cancer therapy (53).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the importance of MAPK in cell proliferation and differentiation, many viruses hijack the MAPK pathway in the progress of virus induced tumor genesis. MAPK was reported to participate in human papillomavirus type (HPV)-induced human cervical squamous carcinoma (29,30). It is hypothesized that HPV infection is one of the histopathologic risk factors in young OSCC patients (1,31).…”
Section: Discussionmentioning
confidence: 99%
“…62,63 systems biology-based virtual cancer pathway prediction and kinetics A literature survey was performed to collect the required information about the selected protein sequences to design and predict the peptides involved in biochemical pathways. [64][65][66][67][68][69][70][71][72][73][74] A mathematical and computational model of the entire HPV45 infection signaling pathway interacting with specific genes in the presence of peptides was developed and was visualized using CellDesigner v4.4 modeling tool. 75 Nodes in the pathway represented the entities, and edges represented connectivity of one node to another, which was closely related to each other.…”
Section: Analysis Of Cross-reactivity With Human Proteomesmentioning
confidence: 99%